(untitled) (Australia, 2007)
The organic chemistry itself is there presenting most major mechanisms in a great step by step arrow pushing format that works very well. Key parts of the mechanism are bold while the non-reactive parts are grayed out making it very easy to follow a reaction even if you are dealing with huge biological molecules.
Keywords: Organic chemistry,Hóa hữu cơ; Textbooks,Sách giáo khoa